Evaluatıon Of Dentofacıal Morphology In Class Iıı Malocclusıon - Sema Yüksel (Galenos Yayinevi, 1996)
In order to evaluate dentofacial morphology and to classify the individuals according to their features, the children with Class III malocclusion was compared to Class I normal occlusion. 189 lateral cephalometric radiographs. of the children aged between 8-13 years were digitized. The dentofacial differences between skeletal Class I and skeletal Class III malocclusion with skeletal Class I normal occlusion were tested with the variance analysis. The classification of the individuals in made by using step wise discriminant analysis. It is identified that Class III individuals have more retrusive maxilla and more protrusive mandible While the incisors have been positioned to compansete Class III structure. The percentage of the correct classification in all groups is found to be 98.41%. 2 cases in Class I malocclusion group and 1 case in Class III malocclusion group have been mis classified. Thus, it has been identified that the individuals with Class III malocclusion can be analized indicated by using discriminant analysis confidently.